2017
DOI: 10.1212/wnl.0000000000004494
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the prevalence of genetic mutations in FTD and ALS

Abstract: Higher female prevalence of hexanucleotide repeat expansions in ALS and mutations in FTD suggest that sex-related risk factors might moderate andmediated phenotypic expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 53 publications
6
32
1
1
Order By: Relevance
“…There were no statistically significant differences between the two groups with respect to median disease duration and male‐to‐female ratio; but there were more women in FTLD‐GRN (57%) than FTLD‐C9ORF72 (27%). This observation fits with a recent meta‐analyses showing that FTLD‐GRN is more common in women than men …”
Section: Resultssupporting
confidence: 93%
“…There were no statistically significant differences between the two groups with respect to median disease duration and male‐to‐female ratio; but there were more women in FTLD‐GRN (57%) than FTLD‐C9ORF72 (27%). This observation fits with a recent meta‐analyses showing that FTLD‐GRN is more common in women than men …”
Section: Resultssupporting
confidence: 93%
“…Interestingly, all of our TIA1 mutations carriers were female, despite there being no sex bias in the case series in which they were identified. This finding is all the more striking, given that ALS, in general, is reported to be more common in men with a ratio of males to females of 1.7:1 [ 21 ] and could indicate that some factor associated with biological sex affects the penetrance of TIA1 mutations, similar to what has been reported for some other genetic subtypes of ALS/FTD [ 6 ]. This association will need to be investigated further in additional case series and we note that one affected member of UBCU2 was male, although no source of DNA was available to confirm his genetic status.…”
Section: Discussionsupporting
confidence: 59%
“…On the contrary, there is a satisfying amount of data that the expansion may be one of the leading genetic causes of HD‐phenocopies in populations of European origin. By comparing the segregate data on prevalence from the reviewed studies to the figures reported in the latest published meta‐analysis of ALS and FTD related to C9orf72 , we noticed a big gap in the observed frequencies and the number of cases, questioning the relevance of C9orf72 to parkinsonian disorders (Fig. ).…”
Section: Resultsmentioning
confidence: 95%